Association of accompanying dyspnea with diagnoses and outcome of patients presenting with suspected acute coronary syndromes. (3rd October 2022) - Boeddinghaus, J; Nestelberger, T; Koechlin, L; Lopez-Ayala, P; Wildi, K; Rubini Gimenez, M; Miro, O; Martin-Sanchez, J; Keller, D; Christ, M; Twerenbold, R; Mueller, C
Abstract: Background: The presence of accompanying dyspnea is routinely assessed and common in chest pain patients with suspected acute coronary syndromes (ACS), but its impact on differential diagnoses, diagnostic work-up and outcome is incompletely understood. Purpose: To determine the association of accompanying dyspnea with diagnoses, diagnostic work-up, and outcome of patients presenting with suspected ACS to the emergency department (ED). Methods: We prospectively enrolled unselected patients presenting to the ED with chest pain as the main symptom suggestive of ACS in an international multicenter study. Final diagnoses were adjudicated by two independent cardiologists using all information including cardiac imaging. Patients were stratified by the presence or absence of self-reported dyspnea. The primary diagnostic endpoint was the differential diagnosis. The secondary diagnostic endpoint was the performance of high-sensitivity cardiac troponin (hs-cTn) and the European Society of Cardiology (ESC) 0/1h-algorithms for the diagnosis of myocardial infarction (MI). The primary prognostic endpoint was all-cause mortality at two years. Results: Among 6045 patients, 2892/6045 (48%) had accompanying dyspnea. Final diagnoses in patients with versus without dyspnea were different (overall p<0.001), but prevalence of ACS was comparable (MI 22.4% vs. 21.9%, p=0.602, unstable angina 8.7% vs. 7.9%, p=0.291). In contrast, patients with dyspnea more often had cardiac, non-coronary disease (15.3% vs. 10.2%, p<0.001). Diagnostic accuracy of high-sensitivity cardiac troponin (hs-cTn)T/I concentrations at presentation for the diagnosis of MI was high and not affected by the presence of dyspnea (area under the curve 0.89–0.91 in both groups). The ESC 0/1h-algorithms performed excellent in both groups with negative predictive values >99.4%. The presence of dyspnea was associated with all-cause death at two years (hazard ratio [HR] 2.487 [95% CI, 2.001–3.091, p<0.001) and remained an independent predictor after adjustment for covariates at baseline (HR 1.813 [95% CI, 1.453–2.261, p=0.001]). Overall mortality rates were higher in patients with dyspnea at two years (9.0% vs. 3.7%, p<0.001). Conclusion: Accompanying dyspnea was not associated with a higher prevalence of ACS but with cardiac, non-coronary disease such as heart failure. While the safety of the diagnostic work-up was not affected, accompanying dyspnea was associated with and an independent predictor for two-year all-cause mortality. Funding Acknowledgement: Type of funding sources: Other. Main funding source(s): Swiss Heart Foundation, University of Basel.